Distribution variability of soil properties of oil palm (Elaeis guineensis) plantations in southern plateau of India - BEHERA, S K; RAO, B N; SURESH, K; MANORAMA, K; RAMACHANDRUDU, K; MANOJA, K (The Indian Journal of Agricultural Sciences, 2015)
The present study was carried out to assess distribution variability of soil properties like pH, electrical conductivity (EC), organic carbon (OC), available potassium (K) (NH4OAc-K), phosphorus (P) (Olsen-P), exchangeable calcium (Ca) (Exch. Ca) and magnesium (Mg) (Exch. Mg), available sulphur (S) (CaCl2-S) and hot water soluble boron (B) (HWB) of oil palm (Elaeis guineensis Jacq.) plantations in southern plateau region of India. The mean values of soil pH, EC(dS/m), OC (g/kg), NH4OAc-K (mg/kg), Olsen-P (mg/kg), Exch. Ca (mg/kg) , Exch. Mg (mg/kg), CaCl2-S (mg/ kg) and HWB (mg/kg) were 6.94 ± 1.19, 0.53 ± 0.47, 11.6 ± 5.60, 179 ± 107, 92.9 ± 50.6, 820 ± 326, 159 ± 58.9, 21.8 ± 14.9 and 5.81 ± 2.53 respectively in surface (0 to 20 cm) soil layers. Geostatistical analysis revealed that surface soil properties had circular, Gaussian, spherical, and exponential best fit models and were influenced by intrinsic, extrinsic and both intrinsic and extrinsic factors. The wide spatial variability of soil properties warrants site specific nutrient management for higher oil palm production.